Artemia Nauplii Enriched with Soybean Lecithin Enhances Growth Performance, Intestine Morphology, and Desiccation Stress Resistance in Yellow Drum (Nibea albiflora) Larvae - Zhenya Zhou; Pian Zhang; Peng Tan; Ruiyi Chen; Weihua Hu; Ligai Wang; Yuming Zhang; Dongdong Xu (Metabolites)
The inherent deficiency of phospholipids in Artemia limits its nutritional value as live prey for marine fish larvae. In our previous study, we optimized a phospholipid enrichment method by incubating Artemia nauplii with 10 g of soybean lecithin per m3 of seawater for 12 h, significantly enhancing their phospholipid content. Purpose: The present study evaluated the impact of this enrichment on yellow drum (Nibea albiflora) larvae, focusing on growth performance, intestinal morphology, body composition, weaning success, and desiccation stress resistance. Methods: The larvae (12 days post-hatching, dph) were fed either soybean lecithin-enriched (SL group) or newly hatched (NH group) Artemia nauplii for 10 days. Results: By the end of the experiment, the SL group exhibited a markedly greater body weight and standard length compared to the NH group (p < 0.05). This growth improvement was due to enhanced intestinal morphology, characterized by a significantly higher mucosal fold height, microvillus density, and microvillus length (p < 0.05). Intestinal RNA sequencing identified 160 upregulated and 447 downregulated differentially expressed genes (DEGs) in the SL group compared to the NH group. Soybean lecithin enrichment reduced the expression of lipogenesis-related genes (fasn, scd, elovl1) while upregulating lipid catabolism genes (ppara, cpt1, cpt2), indicating increased lipid breakdown and energy production. After a 5-day weaning period onto a commercial microdiet, the SL group continued to show significantly superior growth performance. In an afterward desiccation stress test, larvae from the SL group demonstrated significantly higher survival rates, potentially due to the decreased expression of intestinal cytokine genes (ccl13, mhc1, mhc2) observed in the RNA-seq analysis. Conclusions: This study highlights that feeding soybean lecithin-enriched Artemia nauplii enhances growth performance and desiccation stress in yellow drum larvae by promoting lipid catabolism, improving intestinal structure, and regulating immune responses.